Global Health and the New Bottom Billion: What do Shifts in Global Poverty and Disease Burden Mean for Donor Agencies?. Issue 1 (8th October 2012) - Glassman, Amanda; Duran, Denizhan; Sumner, Andy
<x xml:space="preserve">Abstract</x> Abstract After a decade of rapid growth in average incomes, many countries have attained middle income country (MIC) status. At the same time, poverty has not fallen as much as one might expect and as a result most of the world's poor now live in MICs. In fact, there are up to a billion poor people or a 'new bottom billion' living not in the world's poorest countries but in MICs. Not only has the global distribution of poverty shifted to MICs, so has the global disease burden. This article examines the implications of this 'new bottom billion'– the fact that up to a billion of the world's poorest people now live in MICs – for global health efforts, and recommends a tailored middle income strategy for the Global Fund and GAVI. The article describes trends in the global distribution of poverty, preventable infectious diseases, and health aid response to date; revisits the rationale for health aid through agencies like GAVI and the Global Fund; and proposes a new MICs strategy and components, concluding with recommendations. Policy Implications Eliminating the country income threshold as an across‐the‐board criterion for allocating global health funding. Setting up regional pooled procurement or pricing mechanisms. Building evidence based, priority setting institutions in MICs. Establishing increased accountability mechanisms and providing technical support for MICs. Increasing the allocative efficiency of health aid while ensuring equity.